Adaptasi Budaya dan Tantangan Profesional Perawat Indonesia yang Bekerja - Carolintina, Novianna; Malinti, Evelin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze Indonesian nurses' cultural adaptation and professional challenges in the United States. The method used is quantitative descriptive. The results showed that the average level of cultural adaptation was classified as good (mean 18.83). However, the professional challenges faced were classified as high (mean 18.90), especially in workload and communication. There was a strong correlation between cultural adaptation and professional challenges (r = 0.873; p = 0.000), indicating that good adaptation increases awareness of challenges. In conclusion, Indonesian nurses can adapt in the United States, but systemic challenges such as differences in work culture and high workload remain significant. Educational institutions and governments must develop cultural adaptation training, orientation programs, and community support to prepare nurses to work abroad. Keywords: Cultural Adaptation, Nurses, Professional Challenges